Nuclear energy : amazing atoms - Hansen, Amy. (New York : PowerKids Press, 2010)
An introduction to nuclear energy that defines what it is, describes how it is made, and discusses how it is used and its negative effects on the planet.
Energy hiding in atoms -- A closer look at atoms -- Fusion in the sun -- Energy from breaking up -- Making electricity at a nuclear reactor -- Years of study -- Less smoke but still polluting -- Scary accidents -- What is next? -- Nuclear energy timeline -- Glossary.
Includes index.
Library Media Connection
School Library Journal
Library Media Connection, October 2010
School Library Journal, April 2010
5.8
Keywords: Atoms -- Juvenile literature; Nuclear energy -- Juvenile literature; Atoms; Nuclear energy; Atoms; Nuclear energy